PLASMODIUM KNOWLESI - Betta Kurniawan; Jhons Fatriyadi Suwandi; Syazili Mustofa; Sri Janahtul Hayati (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Malaria is a disease which caused by a parasite member of the species of genus Plasmodium. Plasmodium knowlesiis a parasite which found in long-tailed macaques and was firstdiscovered in 1930 from the Macaca fascicularisspeciment from Singapore. In 2004 there was a reported P. knowlesiinfection in humans in Sarawak, Borneo Malaysia and this finding made P. falciparumas the fifth malaria parasite which infect humans. Plasmodium knowlesican sustain its erytrocytic cycle within 24 hours so it can caused a higher infection proggressifity than another parasites. Plasmodium knowlesi’s switch transmission from macaques to human involve some factors, both demographically, environmentaly, and individual behavior.